Kajian Normatif Pengawasan Perbankan Syariah dalam Koridor Hukum Nasional - Ferry Irawan Febriansyah (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Sharia banking supervision is necessary, it is useful to maintain and distinguish between sharia and conventional forms of banking. Positive legal foundations include, among other things, legislation that places Bank Indonesia as the bank supervisory authority. Bank Indonesia is an institution authorized by the government in the supervision of banks in Indonesia including sharia banking, including objective, independent, system and corrective. The Bank Indonesia supervisory mechanism specifically sets forth the rules in Bank Indonesia Regulation Number 11/33 / PBI / 2009 concerning Implementation of Good Corporate Governance for Sharia Commercial Banks and Sharia Business Units which regulates a comprehensive supervisory mechanism in sharia banks covering composition, characteristics, structure and The basic mechanism that must be owned by the Board of Commissioners and the Board of Directors.